Lembar Kerja Siswa Berbasis Pita untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran IPS - Istiqamah Istiqamah; Sriyanto Sriyanto (UM Purwokerto Press, 2022)
Distance Learning during the Covid-19 pandemic that lasted almost nineteen months have brought a negative impact by decreasing students' learning motivation. By allowing the implementation of Limited Face-to-Face Learning, it is necessary to make some efforts to increase students’ learning motivation, one of them is by presenting the interesting teaching materials in the form of Student Worksheets (LKS). This research article aims to describe the PITA based Student Worksheet to improve students’ motivation in Social Studies. The PITA based Student Worksheet is Print teaching materials in the form of sheets of paper containing a summary of the material, presentation of tasks to be done and work steps, equipped with pictures and tables for easy understanding and learning. This research is a descriptive qualitative development reseach. Data collection techniques are carried out through documentation, observations, interviews with VIII grade students of SMP Negeri 3 Wadasintang related to the teaching materials used in the school. Development of PITA based Student Worksheet is structured in four stages, namely 1) analysis, 2) design, 3) development and 4) implementation. The result of this research is in the form of the PITA based Student Worksheet which is adapted to the basic competencies and learning materials. By the use of the PITA Student Worksheet, it is hoped that it can guide students in learning and applying the concepts learned in Social Studies, increase students' learning motivation.